2001
DOI: 10.2118/72061-pa
|View full text |Cite
|
Sign up to set email alerts
|

Application of a New Model To Analyze Leak-Off Tests

Abstract: A leak-off test (LOT), commonly known as a formation-pressureintegrity test, is a verification method to estimate the fracture pressure of exposed formations. After cementing each casing string, a LOT is run to verify that the casing seat can withstand the wellbore pressure required to drill safely to the next casing setting depth. Fracture pressure determined from this test is used as the maximum pressure that may be imposed on that formation. Critical drilling decisions for subsequent casing setting depths a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 1 publication
0
12
0
Order By: Relevance
“…The casing-integrity problem may also arise from the failure of casing shoes. To diagnose such a problem, the formation leakoff test, suggested by Wang et al (2011) and Altun et al (2001), can reveal whether the mud pressure at a certain depth exceeds the ability of the formation to contain it at the casing shoe after cementing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The casing-integrity problem may also arise from the failure of casing shoes. To diagnose such a problem, the formation leakoff test, suggested by Wang et al (2011) and Altun et al (2001), can reveal whether the mud pressure at a certain depth exceeds the ability of the formation to contain it at the casing shoe after cementing.…”
Section: Discussionmentioning
confidence: 99%
“…Prevention of uncontrolled release of hydrocarbons forms the backbone of barrier philosophy in modern well construction and operation. Quoting Norwegian guidelines, Carlsen et al (2010) stated that "well barriers are envelopes of one or several dependent well barrier elements preventing fluids or gases from flowing unintentionally from the formation into another formation or to surface." They cited several reasons for GLV failures, including flow cutting in sealing seats caused by well unloading of completion fluids, the valve-spring fatigue failure, damage during installation, erosion during multiphase or wet gas injection, and damage to valve seat caused by chattering in a low-pressure-drop situation.…”
Section: Introductionmentioning
confidence: 99%
“…Altun et al 2 showed that considering a small section of open hole at the time of a LOT, fluid loss to filtration for a reasonable mud system is a very small volume, particularly in the time frame of a LOT. Hence, filtration losses are not considered.…”
Section: Mathematical Modelmentioning
confidence: 99%
“…The mathematical model developed for an observed physical phenomenon in a closed wellbore system used here is mostly based on the work of Altun et al 2 The derivations for the following correlations can be found elsewhere 2 .…”
Section: Mathematical Modelmentioning
confidence: 99%
See 1 more Smart Citation